A STEP-BY-STEP OVERVIEW OF THE DEPARTMENT OF THE ARMY’S FOOD INSPECTION PROCESS IN FT. RILEY, KANSAS - Deya, Fredrick (My University, 2024)
This report summarizes my Integrative Learning Experience (ILE) at the Public Health Department in Fort Riley, Kansas. The experience lasted for two months, during which I had the opportunity to touch upon every section within the department. My emphasis was on food safety management systems, which are practices implemented by food establishments to ensure that food does not harm consumers along its supply chain. Food contamination occurs due to physical, chemical, and biological hazards such as bacteria, viruses, parasites, fungi, harmful substances (e.g., sanitizers, refrigerant gases), and physical particles (e.g., plastics, wood). These contaminants are often introduced during the receiving, processing, storage, preparation, and serving stages of food distribution. Contamination can result from improper hygiene, sanitation, temperature checks, and cross-contamination caused by food handlers. Consumption of contaminated food can lead to illnesses and fatalities, including salmonellosis (foodborne infection caused by Salmonella spp.), Clostridium perfringens, and Clostridium botulinum, among others . Several studies have proposed different approaches to managing food contamination. At the federal level, key agencies involved in advancing food safety regulatory activities include the Food and Drug Administration (FDA), the Food Safety and Inspection Service (FSIS), the Environmental Protection Agency (EPA), and the National Marine Fisheries Service (NMFS). These federal agencies collaborate with state and private institutions to promote food safety goals. For instance, the FDA's Food Code provides scientific benchmarks and suggestions that states and local administrations can adopt to improve food safety in restaurants and institutional food settings. The code delineates temperature standards for cooking, cooling, refrigerating, reheating, and holding food. Additionally, it advocates for regular inspections of restaurants, recommending a frequency of visits every six months or as deemed necessary.
Keywords: Fort Riley; Public Health; FDA's; Commissary; DFAC; Codex Alimentarius